The Influence of Self-Service Technology on Consumers’ Privacy and Security’s Threats in the Airline Industry - Masran, Nur Hikmah; Abdul Adis, Azaze-Azizi (Malaysian Journal of Business and Economics (MJBE), 2019)
A sophisticated world today is highly characterised based on technology-facilitated transactions that have changed ways the consumers interact with the employees and service providers. It has led to the transformation of service delivery from face-to-face to the use of self-service technology (SST). SST is becoming an important strategic asset for many hospitality organisations, in particular, the airlines industry. The use of SST in the airlines industry has gained enormous momentum in recent years through their company’s website, mobile applications and airport kiosks, etc. However, as the adoption of technological advancement becomes worldly-wise and pervasive, concern on personal information are collected and shared widely with known and unknown entities that often without consumers’ knowledge. These lead to a possibility of compromising the individual’s personal information by third parties. Hence, the main aim of this study is to examine the overall overview of consumers’ privacy and security’s threat as a whole. The main objective is to examine the influence of SST on consumers’ privacy and security’s threat in the airlines industry. Therefore, based on previous studies, this paper will propose a new conceptual framework on the relationship of the influence of SST on consumers’ privacy and will be using Privacy Calculus theory and APCO Model in determining the consumers’ actual disclosure behaviour in the usage of SST. This paper provides consumers with a concise view and knowledge of the influence in using SST towards their privacy and threat’s concern.